2017
DOI: 10.1097/prs.0000000000003349
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of MicroRNA-126 Is a Biomarker for Hemangioma Proliferation

Abstract: Background Hemangiomas are unique endothelial cell tumors that spontaneously involute, which makes it difficult to interpret response to therapies. The objective of this work was to identify a potential biomarker in the urine of children with infantile hemangiomas that would facilitate testing new therapies. Methods A prospective longitudinal study in children with hemangiomas and age matched healthy controls was performed to determine whether microRNA (miR)-126, which is highly abundant in fetal endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…From Strub et al 23 , we selected members of the C19MC microRNAs found in blood that showed changes between pre-treatment and 1 or 6 months of propranolol exposure. Biswas et al 28 reported that microRNA 126 as a biomarker for the proliferative phase of infantile hemangiomas; however, it was not clear from their report which mature form (miR-126-3p or miR-126-5p) was used for their comparisons. In both of the previous studies, microRNA quantification was performed with RT-PCR that precluded us from re-analyzing raw data for better data integration.…”
Section: Resultsmentioning
confidence: 99%
“…From Strub et al 23 , we selected members of the C19MC microRNAs found in blood that showed changes between pre-treatment and 1 or 6 months of propranolol exposure. Biswas et al 28 reported that microRNA 126 as a biomarker for the proliferative phase of infantile hemangiomas; however, it was not clear from their report which mature form (miR-126-3p or miR-126-5p) was used for their comparisons. In both of the previous studies, microRNA quantification was performed with RT-PCR that precluded us from re-analyzing raw data for better data integration.…”
Section: Resultsmentioning
confidence: 99%
“…Biswas et al identified increased urinary levels of miRNA-126 in children with a proliferative hemangioma and managed to establish a proliferation window between six and nine months of age. Afterwards, the levels of miRNA-126 in urine dropped to values encountered in healthy age-matched controls [23].…”
Section:  Genetic Identity Of Ihs Before and After Treatmentmentioning
confidence: 90%
“…RBFOX2 gene is a member of the Rbfox-splicing factors, and it is responsible for the alternative splicing in vascular CaV1.2 channels, which have a regulatory role for intramural pressure change because of blood flow fluctuations [21]. It has been suggested that RBFOX2 could be used as a biomarker, along with Doppler ultrasound in order to establish IH development sites based on expression levels and flow velocities [18,22,23].…”
Section:  Genetic Identity Of Ihs Before and After Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thank you for your thoughtful comments about our recent article, “Urinary Excretion of MicroRNA-126 Is a Biomarker for Hemangioma Proliferation.” 1 The National Institutes of Health Biomarkers Definition Working Group defined a biomarker as “a characteristic that is objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes, or pharmacologic responses to a therapeutic intervention.” 2 There is no requirement that a biomarker represent a singular biologic molecule only found in hemangiomas. The temporal changes in urinary microRNA-126 (miR-126) abundance provided the evidence that miR-126 expression correlates with hemangioma growth with significantly elevated levels during proliferation and no differences with unaffected healthy controls at 9 months of age, when hemangioma proliferation has generally ended.…”
Section: Sirs/madammentioning
confidence: 99%